Telaah Fenomena "Islam Yes, Kafir No" Di Sekolah Dasar Negeri Timuran Yogyakarta Dengan Perspektif Hak Asasi Manusia - Fransiskus, Emanuel; Pandor, Pius (Borneo Review, 2023)
The focus of this research is to explain that the Indonesian Nation, which is known by other nations as the Religious Nation, still harbors the seeds of intolerance and even that is still happening today. The phenomenon related to intolerance this time occurred at the Timuran State Elementary School in the City of Yogyakarta related to the teaching of Islamic pats by scout coaches to elementary school children. This problem went viral some time ago and reaped a lot of responses from netizens and of course it has a negative impact on the integrity of this country which adheres to the ideology of unity. The methodology used in this research is qualitative literature by examining various sources related to the phenomenon under study. The results shown in this study are that when everyone wants to live in peace as brothers and sisters in their country and country, it turns out that there are still many individuals who are actually present by instilling the value of hatred in children who actually become the forerunners of future leaders for the Indonesian nation. It cannot be denied that everyone is free to express themselves, but the freedom that occurs in connection with this phenomenon will only raise new problems, specifically related to the understanding of religion. Collaboration between elements within the school environment, such as the principal, teachers, students, parents and the surrounding community is urgently needed with the aim of avoiding intolerance phenomena and all erroneous beliefs not thriving.